2016
DOI: 10.21873/anticanres.11213
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Proportion of Senescent CD8+ T Lymphocytes During Chemotherapy of Children with Acute Lymphoblastic Leukemia

Abstract: Abstract. Aim: To evaluate quantitative changes in B, NK and T lymphocyte subsets in peripheral blood of children with acute lymphoblastic leukemia (ALL) undergoing chemotherapy. Patients and MethodsAcute lymphoblastic leukemia (ALL) in children is a disease that is effectively cured by the best contemporary protocols (2). Analysis of immune changes in children with ALL undergoing effective chemotherapy would provide an insight as to which of the immune parameters might be related with antitumor effect(s). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Another study exploring the immunomodulatory effects of chemotherapy in pediatric ALL observed a transient decrease in most T lymphocyte subsets during chemotherapy, which was restored by days 78 and 85. However, senescent CD3+CD8+CD57+ lymphocytes did not return to pretreatment levels ( 144 ).…”
Section: Tumor Immune Microenvironment In Bcp-allmentioning
confidence: 99%
“…Another study exploring the immunomodulatory effects of chemotherapy in pediatric ALL observed a transient decrease in most T lymphocyte subsets during chemotherapy, which was restored by days 78 and 85. However, senescent CD3+CD8+CD57+ lymphocytes did not return to pretreatment levels ( 144 ).…”
Section: Tumor Immune Microenvironment In Bcp-allmentioning
confidence: 99%